Private Military Companies’ Role in International Armed Conflicts: A Case Study of Wagner Group's Role in Escalation of the Russia-Ukraine Conflict - Bustami, Sirwan Yazid; Zulkarnain, Zulkarnain (Department of International Relations Universitas Pertamina, 2024)
This research aims to analyze the role of Wagner Group as a private military company in the Russia-Ukraine conflict which is getting deteriorating and has led to a greater conflict escalation. It uses a qualitative approach with an analytical descriptive method. Data was collected through literature review and analyzed through several stages, namely data reduction, data presentation, and conclusion. Data reduction is done by reviewing the collected data to be selected according to research topic. Furthermore, data presentation stage was carried out in form of a narrative. Finally, conclusion is drawn based on elaboration of concept of private military companies and theory of principal–agent. According to research result, it indicates that there is an increase in the intensity of the Russia-Ukraine conflict due to the interference of the Wagner Group. This proves that the principal-agent relationship between Russia and Wagner Group suffers from agency slack. As a consequence, it results in a negative reciprocal relationship, which causes the escalation of conflict to be maintained and provides its own benefits for Wagner Group.